Regulation of the tax duty: comparative characteristic of norm of the Fundamental Law of Ukraine and Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
Regulation of tax obligation has been investigated on the basis of comparative characteristics of norms of the Fundamental Law of Ukraine and Republic of Kazakhstan. The common denominators and differences have been defined in the regulation of obligation for taxes and fees payment in Ukraine and Republic of Kazakhstan by analyzing Constitutions of both countries. Optimization lines of norms of the Fundamental Law of Ukraine and Republic of Kazakhstan have been suggested.
Keywords: duty of taxpayer; tax obligation; taxpayer; paying taxes; tax declaration; constitutional duty; constitutional norm